Estetika Pojok Baca Ruang Kelas Anak Usia Dini - Heri Hidayat; Oktaviah Amaliah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2022)
This research is intended to find out observations related to the level of aesthetic observation in a classroom that has a reading corner. The corner reading is an activity carried out by children in every spare time during recess or when learning is centered on reading to read books that have been provided on the shelf. In this case the problem contained in this study about how the author's view of the aesthetics of a room is a reading corner that has been found various varieties from google picture and youtube sources by making observations in accordance with aesthetic levels 1 to aesthetic level 3. The research method used is a method of literature study that research materials are obtained from the literature study of reading and recording results so that the results of research are the five objects have an interesting beauty and different of course by being equipped with elements and components to each image that make it appear to be esetic according to its aesthetic level.